Can addiction counselors be trained to deliver Mothering from the Inside Out, a mentalization-based parenting therapy, with fidelity? Results from a community-based randomized efficacy trial. Issue 3 (3rd May 2020) - Suchman, Nancy E.; Borelli, Jessica L.; DeCoste, Cindy L.
ABSTRACT: This study evaluated methods for training community-based clinicians to deliver a mentalization-based parenting intervention in an addiction treatment setting. Mothering from the Inside Out (MIO) targets psychological deficits associated with early stages of addiction recovery by fostering improvement in parental reflective functioning, the capacity to make sense of strong emotions in oneself and the child. Fifteen addiction counselors were randomized to training in MIO versus a Parent Education comparison, and completed eight training sessions and a clinically-supervised 12-session training case. As predicted, MIO and PE counselors demonstrated fidelity to their respective interventions during the training case. At the end of training, MIO counselors showed greater improvement than PE counselors in clinical reflective functioning, the capacity to make sense of a patients' mental and emotional experiences. Implications for training community-based counselors in evidence-based attachment interventions are explored.